2017
DOI: 10.2340/00015555-2447
|View full text |Cite
|
Sign up to set email alerts
|

Antipruritic Effect of Cold-induced and Transient Receptor Potential-agonist-induced Counter-irritation on Histaminergic Itch in Humans

Abstract: A frequent empirical observation is that cold-induced counter-irritation may attenuate itch. The aim of this randomized, single-blinded, exploratory study was to evaluate the counter-irritation effects of cold-stimulation and topical application of transient receptor potential TRPA1/M8-agonists (trans-cinnamaldehyde/L-menthol, respectively), on histamine-induced itch, wheals and neurogenic inflammation in 13 healthy volunteers. Histamine 1% was applied to the volar forearms using skin prick-test lancets. Recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 66 publications
(99 reference statements)
2
28
1
Order By: Relevance
“…As a result, the study was not directed towards quantifying the histaminergic itch, that is, both histamine-induced itch provocations were performed and assessed simultaneously, histamine were delivered close to the capsaicin injection by i.d. Given that even mild homotopic painful stimuli are capable of greatly reducing itch (Graham et al, 1951;Yosipovitch et al, 2005Yosipovitch et al, , 2007Kosteletzky et al, 2009;Andersen et al, 2017a), it is hard to evaluate whether the observed itch reduction was related to capsaicin-induced secondary sensitization or simply ongoing counter-stimulation. Applying this methodology, the study reported that only 2/8 tested subjects reported itch when histamine injections were given in allodynic skin as opposed to normal skin, which is in some accordance with the reduction in itch sensation observed in the present experiment.…”
Section: Decreased Itch In a Capsaicin-evoked Allodynic And Hyperalgementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the study was not directed towards quantifying the histaminergic itch, that is, both histamine-induced itch provocations were performed and assessed simultaneously, histamine were delivered close to the capsaicin injection by i.d. Given that even mild homotopic painful stimuli are capable of greatly reducing itch (Graham et al, 1951;Yosipovitch et al, 2005Yosipovitch et al, , 2007Kosteletzky et al, 2009;Andersen et al, 2017a), it is hard to evaluate whether the observed itch reduction was related to capsaicin-induced secondary sensitization or simply ongoing counter-stimulation. Applying this methodology, the study reported that only 2/8 tested subjects reported itch when histamine injections were given in allodynic skin as opposed to normal skin, which is in some accordance with the reduction in itch sensation observed in the present experiment.…”
Section: Decreased Itch In a Capsaicin-evoked Allodynic And Hyperalgementioning
confidence: 99%
“…The pronounced and well-documented inhibition of itch by homotopic pain can be readily elicited, for example, by scratching or by applying noxious heat stimuli in an area with ongoing itch (Graham et al, 1951;Yosipovitch et al, 2005Yosipovitch et al, , 2007Kosteletzky et al, 2009;Andersen et al, 2017a). This inhibitory mechanism is suggested to rely on spinal basic-helixloop-helix B5-interneurons and a population of vesicular glutamate transporter type 2-expressing neurons activated by nociceptive stimuli and inhibiting spinal transmission of pruriceptive signaling (Lagerstr€ om et al, 2010;Liu et al, 2010;Ross et al, 2010;Ross, 2011).…”
Section: Mechanisms Of Pain-and Sensitizationinduced Itch Inhibitionmentioning
confidence: 99%
“…However, numerous studies suggest that homotopic innocuous and noxious cooling, or cooling compounds are capable of suppressing itch, and patients with chronic itch frequently report that cooling relieves their itch. 21,50,68,69 This warrants further investigation. In experiment 2, itch intensity without any counterstimuli was not assessed.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the effect of transient cold stimuli was not investigated in this study due to technical limitations. However, numerous studies suggest that homotopic innocuous and noxious cooling, or cooling compounds are capable of suppressing itch, and patients with chronic itch frequently report that cooling relieves their itch . This warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1, TRPV4, and TRPV3 expressions were increased in burn scars with postburn pruritus [101]. Although, in terms of pharmacological activity, science differentiates between cooling and heating pungent compounds: cooling pungent compounds (TRPM8 agonists, e.g., menthol) ameliorate pruritus [322], while heating pungent compounds (TRPV1 agonists, capsaicin) aggravates it [323]. Scientists had recently suggested that agonists of cold transduction receptors might have antipruritic potential [322].…”
Section: Traditional Taste (Rasa) In the Light Of Modern Sciencementioning
confidence: 99%